Platelet-Derived Microparticle Count in β-Thalassemia Patients with Direct Labeling Monoclonal Antibody CD62P and CD41 - Ivan Lumban Toruan; Pandji Irani Fianza; Delita Prihatni (Majalah Kedokteran Bandung, 2020)
Thromboembolic events are potentially life-threatening clinical complications found in β-thalassemia patients. The pathogenesis of the hypercoagulable state in β-thalassemia patients results from the degradation of excess α-globin chains in red blood cells, leading to intracellular labile iron accumulation, oxidative stress, and more rigid, deformed, and eventually prematurely damaged red blood cells. This process is associated with the loss of the normal asymmetrical distribution of membrane phosphatidylserine and its exposure to the outer surface of the blood cell membrane resulting in the formation of tenase complexes, prothrombinase, and thrombin complexes. Increased thrombins lead to platelet activation and platelet-derived microparticles synthesis, which in turn contributes to thrombus formation. This study aimed to determine the increase in the platelet-derived microparticle count by direct labeling of CD62P and CD41 monoclonal antibodies in β-thalassemia patients when compared with normal subjects. This was a cross-sectional analytical quantitative study conducted in Dr. Hasan Sadikin General Hospital Bandung and Dharmais Cancer Hospital Jakarta Indonesia between August and September 2019. Sixty patients, divided evenly into β-thalassemia group and control group, were labeled by CD62P and CD41 monoclonal antibodies. Results showed that the β-thalassemia group had a platelet count of 197x103/uL (58–1,261) with a median count for platelet-derived microparticles of 10,553 events/uL (779–90,971) as opposed to 1,861 events/uL (1,244–3,174) in the normal group (p<0.05). Therefore, the platelet-derived microparticle count in the β-thalassemia patients is 5.7 times greater than in the normal subjects.Jumlah Platelet Derived Microparticles pada Pasien Thalassemia β dengan Metode Pelabelan Langsung Antibodi Monoklonal CD62P dan CD41Kejadian tromboemboli berpotensi komplikasi klinis yang mengancam jiwa ditemukan pada pasien thalassemia β. Patogenesis keadaan hiperkoagulasi pada pasien thalassemia β akibat dari degradasi rantai globin α berlebih dalam sel darah merah yang menghasilkan akumulasi besi labil intraseluler, dan mengarah pada stres oksidatif serta sel darah merah yang lebih kaku dan cacat, dengan akibat kerusakan prematur. Proses ini dikaitkan dengan hilangnya distribusi asimetris normal dari fosfatidilserin membran dan paparannya pada permukaan luar membran sel darah, yang meyebabkan pembentukan kompleks tenase, kompleks protrombinase dan trombin. Peningkatan trombin mengarah pada aktivasi trombosit dan sintesis platelet derived microparticles yang selanjutnya berkontribusi pada pembentukan trombus. Tujuan dari penelitian ini adalah mengetahui peningkatan jumlah platelet derived microparticles dengan metode pelabelan langsung antibodi monoklonal CD62P dan CD41 pada pasien thalassemia β dibanding dengan subjek normal. Penelitian ini merupakan suatu penelitian kuantitatif dengan metode analitik potong lintang yang dilakukan di RSUP Dr. Hasan Sadikin Bandung dan Rumah Sakit Kanker Dharmais Jakarta antara bulan Agustus dan September 2019. Enam puluh pasien, dibagi secara merata menjadi kelompok thalassemia β dan kelompok kontrol, diberi label oleh CD62P dan CD41 antibodi monoklonal. Hasil penelitian menunjukkan kelompok thalassemia β memiliki jumlah trombosit 197x103/uL (58–1.261) dengan jumlah median platelet derived microparticles 10.553 partikel/uL (779–90.971) dibanding dengan 1.861 partikel/uL ( 1,244–3,174) pada kelompok normal (p<0,05). Simpulan, jumlah platelet derived microparticles  pada pasien thalassemia β adalah 5,7 kali lebih besar daripada pada subjek normal.